Multimodal gadolinium oxysulfide nanoparticles: a versatile contrast agent for mesenchymal stem cell labeling. Issue 35 (29th August 2018) - Santelli, Julien; Lechevallier, Séverine; Baaziz, Houda; Vincent, Marine; Martinez, Cyril; Mauricot, Robert; Parini, Angelo; Verelst, Marc; Cussac, Daniel
Abstract : Despite a clear development of innovative therapies based on stem cell manipulation, the availability of new tools to better understand and follow stem cell behavior and improve their biomedical applications is not adequate. Abstract : Despite a clear development of innovative therapies based on stem cell manipulation, the availability of new tools to better understand and follow stem cell behavior and improve their biomedical applications is not adequate. Indeed, an ideal tracking device must have good ability to label stem cells as well as complete neutrality relative to their biology. Furthermore, preclinical studies imply in vitro and in vivo approaches that often require several kinds of labeling and/or detection procedures. Consequently, the multimodality concept presented in this work may present a solution to this problem as it has the potential to combine complementary imaging techniques. Spherical europium-doped gadolinium oxysulfide (Gd2 O2 S:Eu 3+ ) nanoparticles are presented as a candidate as they are detectable by (1) magnetic resonance (MRI), (2) X-ray and (3) photoluminescence imaging. Whole body in vivo distribution, elimination and toxicity evaluation revealed a high tolerance of nanoparticles with a long-lasting MRI signal and slow hepatobiliary and renal clearance. In vitro labeling of a wide variety of cells unveils the nanoparticle potential for efficient and universal cell tracking. Emphasis on mesenchymal stromal cells (MSCs) leads to the definition of optimal conditions for labeling and tracking in the context of cell therapy: concentrations below 50 μg mL −1 and diameters between 170 and 300 nm. Viability, proliferation, migration and differentiation towards mesodermal lineages are preserved under these conditions, and cell labeling appears to be persistent and without any leakage. Ex vivo detection of as few as five thousand Gd2 O2 S:Eu 3+ -labeled MSCs by MRI combined with in vitro examination with fluorescence microscopy highlights the feasibility of cell tracking in cell therapy using this new nanoplatform.